Screening and Biodegradation of Polycyclic Aromatic Hydrocarbons by Indigenous Endophytic Fungi - Dalene, Lesen (Universiti Malaysia Sarawak (UNIMAS), 2019)
Phenanthrene is a type of polycyclic aromatic hydrocarbon (PAH). It is an organic pollutant that exists persistently in the environment, resulting mainly from anthropogenic activities. Out of the 24 different fungi that had been successfully isolated from water hyacinth (Eicchornia crassipes), 5 fungal isolates showed the ability to degrade phenanthrene. Isolates EC08 and EC22, showed higher rate of phenanthrene degradation as compared to isolates EC04, EC13, and EC18. Percentage of phenanthrene degradation of EC08 and EC22 after 7 days was shown to be 8.26% and 14.19%, respectively. All five isolates showed the presence of manganese peroxidase (MnP), lignin peroxidase (LiP), and laccase (Lacc) activities in the presence of phenanthrene. The magnitude of the enzyme activities did not correlate with the percentage of phenanthrene degradation by the fungi. This suggests that other enzymes apart from the ligninolytic enzymes might be involved in the degradation pathways, and that the phenanthrene degradation involves a complex multienzymatic system. The physical and chemical parameters that can affect the growth of fungi and the rate of phenanthrene degradation were studied. It was observed that, each of the isolate showed different preferences in the pH of the growth media, the supplemental carbon, as well as the supplemental nitrogen. Identification of the five isolates was done based on their morphology as well as through molecular analysis. Through the analysis, isolates EC04, EC08, and EC22 were identified as Phlebia acanthocystis, Penicillium pinophilum, and Aspergillus versicolor respectively, while isolates EC13 and EC18 were identified as Inonotus pachyphyleous T61 and Inonotus pachyphloeus RS1, respectively.